Lima: The indigenous, the viceregal, the modern Very brief urban history of the City of Los Reyes - Scaletti Cárdenas, Adriana (2020)
The history of the Lima city is also the history of its blueprint and its urban network. From the humble initial settlement, going through extensions planned with care and order, to the complex and chaotic situation of the present, we can speak of a particular physical history and in many aspects exceptional: a reflection and product of the society that produced it, the ancient city of Los Reyes remains as it can be perceived today, in many quotidian ways, but not for that less determining.